Assessment of Price Adjustment Mechanisms in Romanian Public Construction Contracts: A Longitudinal Cost Impact Analysis (2018–2024) - Cornel Adrian Ciurușniuc; Irina Ciurușniuc-Ichimov; Adrian Alexandru Șerbănoiu (Buildings)
Since the enforcement of Law 98/2016 on public procurement in Romania, the inclusion of price adjustment clauses in construction contracts has become a standard practice. This paper, which presents a comprehensive analysis of the financial implications of eight adjustment formulas applied to public construction projects executed over three durations (12, 24, and 36 months) between 2018 and 2024, is a significant contribution to the field. A comparative analysis using objective indices published by Romania’s National Institute of Statistics reveals the impact of inflation and cost variations on adjusted contract values. Three scenarios, each starting in different years (2018, 2020, and 2022), are explored to determine the sensitivity of the formulas to market fluctuations. Results show that by applying the eight adjustment formulas, only two formulas tend toward annual inflation. The indices used by the construction branch are not correlated with yearly inflation, and when no advance payments are granted, they offer a reliable basis for economic equilibrium in public contracting. The study guides the selection of appropriate adjustment models to manage financial risk in a volatile construction market, providing valuable insights for academics, researchers, and professionals in civil engineering and public procurement.